ANALISIS IMPLEMENTASI KEBIJAKAN PENCEGAHAN KONFLIK SOSIAL MELALUI BADAN KESATUAN BANGSA DAN POLITIK KOTA BANDUNG - Artamevia, Regina Layla; Afandi, Muhamad Nur; Nurliawati, Nita; Sudrajat, Achmad Sodik (Jurnal Progress Administrasi Publik, 2025)
Social conflict prevention is a crucial aspect in maintaining social stability and harmony. This study aims to analyze the implementation of social conflict prevention policies carried out by the Bandung City Agency for National Unity and Politics (Bakesbangpol), with a focus on the early warning function. Referring to Law No. 7 of 2012 on the Handling of Social Conflicts, which regulates the government’s obligation to conduct early detection, prevention, and post-conflict recovery, this study employs a qualitative method using George C. Edwards III’s (1980) policy implementation model. The results show that although Bakesbangpol has made various efforts in preventing social conflict, challenges remain, such as limited human resources and budget constraints. The study recommends several strategic steps to improve policy implementation, including the development of an integrated information system for conflict monitoring, the use of technology for early detection, and community-based empowerment involving local leaders and organizations. These measures are expected to create a safer and more harmonious environment in Bandung City and maintain social stability amidst complex societal dynamics.   Keywords: ; Implementation; Public Policy; Social Conflict